Application of Fuzzy Sets Function for Land Attributes Mapping - Dwi Putro Tejo Baskoro (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2008)
A study was conducted to evaluate the potential use of Geographical Information System (GIS) for mapping thebiophysical resources of watershed PC-based GIS soft-wares were used in the analysis, processing and mapping of spatialdata. The conventional mapping technique that presents land attribute in form of polygon with abrupt change across classboundaries was improved using Fuzzy technique. This technique involves the generation of membership maps for each soiltype based on the relationship between the soil type and it's forming factors like geology, elevation, slope gradient, slopeaspect, slope curvature, and land cover. The fuzzy technique was found to be more appropriate than the conventionaltechnique of mapping in expressing continuous and gradually changing soil or land attributes. Validation with observed soilor land attributes values indicated that root mean square error (RMSE) obtained for Fuzzy method was lower than that fromthe conventional method